Factorial Structure of Community Intervention Strategies in Ecotourism - VINODAN, A.; MANALEL, James; MEERA, S. (Journal of Environmental Management and Tourism, 2017)
The purpose of this paper is to identify existence of various community intervention strategies (CIS) and its’ dimensional orientation of community based ecotourism (CBE) destinations of India. The study adopted exploratory sequential method, employed focus group, interview and structured questionnaire for primary data collection. Exploratory factor analysis was done for identifying dimensions of CIS. Data gathered from four Protected area (PA) based ecotourism destinations of Kerala, India, viz Thenmala, Periyar, Parambikulam and Wayanad. The results indicate that there are 16 intervention strategies widely practiced in CBE destinations of India. All these 16 intervention strategies have three distinct dimensions consist of governance, ecodevelopment and commercial, which underline the diversified way of intervening in resource management practices at ecotourism destinations.